Changes in the microRNA expression profile during blood storage. Issue 1 (5th July 2018) - Haberberger, Anna; Kirchner, Benedikt; Riedmaier, Irmgard; Henschler, Reinhard; Wichmann, Christian; Buhmann, Raymund; Pfaffl, Michael W
Abstract : Objectives: For several decades, autologous blood doping (ABD) in sports has been a major problem, and even today there is still no reliable method for satisfactorily detecting ABD. For this kind of doping, stored individual erythrocytes are used to increase stamina and endurance caused by a higher erythrocyte level in the athlete's body. Since there is growing evidence that these cells are enriched with microRNAs (miRNAs), this study has been carried out to discover and validate all miRNAs occurring in fresh blood as well as in stored blood. Methods: Therefore, small RNA Next Generation Sequencing has been performed, which allows untargeted detection of all miRNAs in a blood sample. The focus of this investigation has been to find miRNA alterations in blood bags after erythrocyte processing and during storage, as compared with fresh blood directly withdrawn from subjects. Blood samples were obtained from 12 healthy, recreationally active male subjects three times before blood donation and from blood bags at several time points after blood processing. Results: 189 miRNAs have been considered stable over two consecutive weeks. A further analysis revealed a complex biomarker signature of 28 miRNAs, consisting of 6 miRNAs that altered during 6 weeks of storage and 22 miRNAs that altered due to processing. Conclusion: These results suggest that the identified miRNA biomarker signature may be used for the detection of ABD. These 28 miRNA candidates are tested and verified currently in a follow-up study, a human transfusion clinical trial in healthy sportsmen.